Memorial dedicated to Henry Robertson Bowers - Ghosh, Ayan (2023)
Memorial dedicated to Henry Robertson Bowers, Lieutenant of the Royal Indian Marine, who lost his life on the ill-fated British Antarctic Expedition of 1910–1913, led by Captain Robert Falcon Scott (1868-1912). The team intended to be the first to reach the geographic South Pole but was beaten to the race by Roald Amundsen's polar party. Bowers, Scott, and other members of the party ran out of food and perished on the return journey sometime around 27 March 1912.